1986
DOI: 10.1159/000156249
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Karyotypes of Six Species of the Genus Macaca and a Species of the Genus Cercocebus

Abstract: Karyotypes from 72-hour whole blood cultures were compared for six species of macaques (Macaca arctoides, M. fascicularis, M. mulatta, M. nemestrina, M. nigra, and M. radiata) and one species of mangabey (Cercocebus atys). G-bands, sequential C-bands, and late replication patterns were studied. Results showed a variation in a single chromosome pair which differentiated C. atys from the macaques. Heteromorphic variation in silver stained nucleolar organizing regions was seen between and within individuals. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
3
17
1
Order By: Relevance
“…The genetic marker of the macaque in genus Macaca in Thailand is NOR on the short arm of chromosome 13. This result agrees with the result from Brown et al (1986) that reported M. arctoides, M. fascicularis, M. mulatta, M. nemestrina, Celebes crested, Bonnet and Mangabey have NOR on the short arm of chromosome 9. The different position of NOR occurred because of the karyotype and the method used to detect the length of the chromosome.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The genetic marker of the macaque in genus Macaca in Thailand is NOR on the short arm of chromosome 13. This result agrees with the result from Brown et al (1986) that reported M. arctoides, M. fascicularis, M. mulatta, M. nemestrina, Celebes crested, Bonnet and Mangabey have NOR on the short arm of chromosome 9. The different position of NOR occurred because of the karyotype and the method used to detect the length of the chromosome.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the autosomes were different from Brown et al (1986) who reported that M. arctoides has 14 metacentric and 26 submetacentric chromosomes whereas the chromosomes of M. fascicularis, M. mulatta and M. nemestrina were similar, with 18 metacentric and 22 submetacentric. M. fascicularis (Hirai et al 1991) and M. mulatta (Napier andNapier 1976, Small andStanyon 1985) are also reported as having 18 metacentric and 22 submetacentric chromosomes.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations